Self-assembly of sandwich-type (phthalocyaninato)(porphyrinato) europium double-decker complexes: Effects of hydrogen bonding on intermolecular stacking mode and morphology of self-assembled nanostructures. (February 2015) - Lu, Jitao; Zhou, Liang; Meng, Qingguo; Sui, Haiyan; Li, Yi; Tai, Xishi
Abstract: Two novel sandwich-type (phthalocyaninato)(porphyrinato) europium double-decker complexes, namely Eu(Pc)[(NHC8 H17 )PP] (1 ) and Eu(Pc)[(NHC8 H17 )4 PP] (2 ), have been designed and synthesized. Their self-assembly properties, in particular the effect of the numbers of octylaminophenyl groups on the morphology of self-assembled nanostructures of these double-decker complexes, have been comparatively and systematically studied. Depending mainly on the hydrogen bond between one octylaminophenyl group at meso -attached phenyl group of porphyrin ligand in1 and one aza-nitrogen atom of the phthalocyanine ring in the neighboring molecule of1, 1 self-assembled into nano-rods with J -type aggregation. In good contrast, introduction of four octylaminophenyl groups onto the m eso -attached phenyl groups of the porphyrin ligand in2, induces more N–H⋯N hydrogen bonds between neighboring molecules of2, induces the formation of nano-sheets with H -type aggregation. These results clearly imply the effective influence of hydrogen bond numbers on the molecular stacking mode and the morphology of the assembled nanostructures. Graphical abstract: Comparative investigation over self-assembled nano-structures of two novel sandwich-type (phthalocyaninato)(porphyrinato) europium double-decker complexes with one and four octylaminophenyl group attached at the p -position of the m eso -attached phenyl group of the porphyrin ligand reveals the effect of inter-molecular hydrogen bonds on the molecular packing conformations and in turn different nanostructure morphologies in the self-assembly process. Highlights: Two (phthalocyaninato)(porphyrinato) europium double-decker complexes were prepared. Effect of the number of hydrogen bonds on the assembled nanostructures was studied. Both nano-rods and nano-sheets were revealed to show good semiconductor features.